Upaya Perlindungan Hukum Terhadap Wanita Yang Ditinggal Oleh Suami Siri: Perspektif Hakim Pengadilan Agama Serdang Bedagai - Clarita, Alicia Dita; Irwan, Irwan (Jayapangus Press, 2025)
There are many negative impacts resulting from unregistered marriages, but many still carry out unregistered marriages for various reasons. This causes many problems that occur after the unregistered marriage, both in terms of status and income. The problem that often occurs is the husband leaving the house, causing uncertainty about the wife’s status, and resulting in the child not being provided for by her husband. This research aims to analyze legal protection for the livelihood and status of women who are abandoned by married husbands by revealing facts about the views of the judges of the Serdang Bedagai Religious Court regarding the status and resolution of existing problems. This research method is a qualitative method with a case study approach. This research is descriptive qualitative in nature where the author examines the applicable legal provisions and what happens in reality in society. Siri marriage as known to Indonesian society today is a marriage that is carried out in compliance with the pillars and requirements set by religion, but is not legally valid. The results of this research are regarding legal protection regarding status and income to be earned as well as efforts that can be made to clarify and obtain the income that should be obtained. The solution or legal protection effort offered by the judge at the Serdang Begagai religious court for women living with their married husbands who want to clarify their marital status and themselves is by filing a lawsuit. With the name of the lawsuit, namely the legalization of marriage cumulated with divorce or isbat marriage cumulated with divorce lawsuit. And to get a living for himself and the children from the unregistered marriage, namely the accumulation of divorce cases with alimony.